Préfigurations du lecteur dans la presse en ligne - Alexandra Saemmer (Communication)
How does an online journalism text displayed on a screen page and embedded in a socio-technological dispositive come to prefigure its “model audiences”? The author draws on the analytical tools of cultural studies and political economy to establish the methodological foundation for a semiotic-rhetorical investigation of media text. The core material for the study is a corpus of articles published on liberation.fr and lemonde.fr in 2014 about the cancellation of Dieudonné’s stand-up comedy show and the disclosure of President François Hollande and Julie Gayet’s secret relationship. The author shows how journalists prefigure “model audiences” through the configuration of the screen page and the use of hyperlinks, while grounding her analysis in a critical approach to media study.